Tinjauan Literatur Sistematis; Pemanfaatan Teknologi CRISPR-CAS9 Untuk Pengobatan Penyakit Huntington’s - Sari, Meliana; Kasasiah, Ahsanal (Media Farmasi, 2024)
Huntington's Disease (HD) is a neurodegenerative disorder caused by a CAG triple expansion (>36) in the first exon of the HTT gene encoding the huntingtin protein. Advances in gene editing technologies, such as CRISPR-Cas9, provide new hope for correcting the genetic mutations underlying HD. This review article aims to review the potential and effectiveness of CRISPR-Cas9 technology as a therapeutic tool for HD. The writing method used was Systematic Literature Review, with literature searches conducted using three databases: PubMed, ScienceDirect, and SpringerLink. This study reviewed several studies that used in vivo and in vitro models to evaluate the impact of HTT gene editing on mutant huntingtin protein expression and HD symptoms. Results showed that CRISPR-Cas9 can effectively reduce mutant huntingtin protein expression, reduce neuronal toxicity, and improve motor symptoms in mouse models of HD. Although these results are promising, further studies are needed to optimize the safety and effectiveness of using CRISPR-Cas9 in genetic therapy for HD.